NETWORK FEATURES IN THE ORGANIZATION OF THE ANALYSIS - Norbuta E. Babakhalov (International Scientific and Current Research Conferences, 2022)
This article is devoted to the issues Network features in the organization of the analysis. Therefore, in our opinion, these aspects should be taken into account when describing the economic analysis according to the industry principle. That is, as shown in the figure, it is controversial to include economic analysis in the cross-industry analysis in the description of the economic analysis.